A snapshot of patients' awareness of radiation dose and risks associated with medical imaging examinations at an Australian radiology clinic. Issue 2 (May 2017) - Singh, N.; Mohacsy, A.; Connell, D.A.; Schneider, M.E.
Abstract: Background: Cumulative radiation exposure is linked to increasing the lifetime attributable risk of cancer. To avoid unnecessary radiation exposure and facilitate shared decision making, patients should be aware of these issues. This paper examines patients' awareness of radiation dose and risks associated with medical imaging examinations. Methods: Consecutive patients attending a private radiology clinic over a nine week period in 2014 in Metropolitan Melbourne were surveyed while waiting to undergo an imaging examination. Patients who were under 18 years of age, did not speak English and/or were referred for interventional imaging procedures were excluded from participation. Survey questions addressed patients' awareness of radiation dose associated with various imaging modalities' and patients' experience and preferences regarding communication of information about radiation. Data was analysed using SPSS (Ver 20.1). Results: A total of 242 surveys were completed. Most participants were male (143/239, 59.8%) and aged between 33 and 52 years (109/242, 45%). Over half of participants were not concerned about radiation from medical imaging (130/238, 54.6%). Only a third of participants (80/234, 34.2%) correctly reported that CT has a higher radiation dose than X-ray. Very few participants correctly identified mammography, DEXA, PET and PET/CT as radiation emitting examinations. The majority of participants (202/236, 85.6%) indicated that they were not informed about radiation dose and risks by their referring doctor in advance. Conclusion: This paper provides information relevant to a single private radiology clinic in Australia. Nevertheless, our results have shown that patients presenting for medical imaging have little awareness of radiation dose and risks associated with these examinations and received little information by their referring physicians or staff at the radiology clinic. Highlights: Patients' awareness regarding imaging radiation dose and risks is overall poor. Most patients receive little to no information by their referring doctor regarding dose and risks. Awareness of dose and risks can facilitate shared decision making and reduce unnecessary radiation exposure. Findings may guide future initiatives to improve patients' awareness of dose and risks.